The Problematics of Paulo Freire's Concept of Humanist Education from an Islamic Perspective - Nurhasanah, Muwahidah; Idharudin, Abdul Jabar; Darmanto, Darmanto; Alfin, Khusna Zanuba (Al-Lubab : Jurnal Penelitian Pendidikan dan Keagamaan Islam, 2024)
Paulo Freire's humanist education emphasizes critical consciousness and the liberation of humanity from oppression. However, this approach is often criticized for being insufficiently comprehensive, as it overlooks the spiritual dimensions and the concept of adab (ethics), which are central to Islamic education. This study aims to analyze the problems within Freire's humanist education concept from an Islamic perspective, focusing on conflicts in the value of freedom, neglect of spirituality, the teacher's role in dialogue, and the ultimate goals of education. This research employs a library research methodology with a qualitative descriptive approach. Data were analyzed through a critical review of relevant primary and secondary literature, including Freire’s works, Islamic educational thought, and previous studies. The findings reveal fundamental shortcomings in Freire’s educational approach from the Islamic perspective, such as a secular view of freedom, neglect of spirituality, and a lack of emphasis on adab and tawhid (monotheism). However, integrating Freire’s concept with Islamic values shows potential for creating a holistic educational paradigm. This integration harmonizes critical awareness with moral and spiritual responsibility, providing solutions to global educational challenges. Research implications/limitations: This study offers new insights into the possible integration of Freire’s and Islamic education concepts, though it is limited to theoretical exploration without empirical testing. Further studies are needed to examine its application in formal and informal educational settings. This research provides a novel perspective by combining two contrasting educational approaches: progressive humanism and value-based Islamic education. The findings are relevant for developing curricula responsive to contemporary social and spiritual challenges.